2020
DOI: 10.1111/dth.14628
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of depression and impairment in quality of life in patients with lamellar ichthyosis

Abstract: Lamellar ichthyosis (LI) is a genetic skin disorder characterized by dark brown scales, palmoplantar hyperkeratosis, pain, and itching. LI severity could have implications in psychological aspects, causing depression and impairment in the quality of life (QoL) of patients. In this study, we used the Congenital Ichthyosis Severity Index, the Depression Beck Inventory‐II (DBI‐II), and the Dermatologic Life Quality Index (DLQI) to assess severity, level of depression, and impairment in QoL in a group of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Likewise, we recently conducted a casecontrol study with 26 patients with ARCI and 26 healthy volunteers. 37 We evaluated the severity of symptoms (CISI scale), the presence of depression (the Beck Depression Inventory), and the QoL (DLQI) impairment in those patients. We found that ARCI patients exhibited an increased risk of suffering from depression (80% of patients showed depression vs. 20% of control individuals) and impairment in their QoL.…”
Section: Ichthyosismentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, we recently conducted a casecontrol study with 26 patients with ARCI and 26 healthy volunteers. 37 We evaluated the severity of symptoms (CISI scale), the presence of depression (the Beck Depression Inventory), and the QoL (DLQI) impairment in those patients. We found that ARCI patients exhibited an increased risk of suffering from depression (80% of patients showed depression vs. 20% of control individuals) and impairment in their QoL.…”
Section: Ichthyosismentioning
confidence: 99%
“…Remarkably, both studies revealed a statistically significant correlation between QoL and mental health because patients that suffered a more considerable impact on their QoL presented with higher levels of anxiety and depression. 7,37 However, the depression and DLQI scores will also depend on the country's development, geographic region, educational status, socioeconomic profile, religion, age, and sex.…”
Section: Ichthyosismentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 The correlates of rarer skin conditions such as the inherited ichthyoses, which are characterized by abnormal keratinization, 25 are comparatively less well-defined, although there is recent evidence that across the ichthyoses, rates of psychological distress are raised while QoL is diminished. 26,27 Qualitative data have suggested that QoL impairment in inherited ichthyoses may be due to a combination of factors, including physical health, daily life issues, and relationships with oneself and others. 28 As the ichthyoses have differences in aetiology, severity and epidemiology, there is a need to study each separately.…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis has been associated with a substantially increased risk of depression or anxiety disorders 21,22 and neurodevelopmental conditions, notably autism spectrum disorder 23,24 . The correlates of rarer skin conditions such as the inherited ichthyoses, which are characterized by abnormal keratinization, 25 are comparatively less well‐defined, although there is recent evidence that across the ichthyoses, rates of psychological distress are raised while QoL is diminished 26,27 . Qualitative data have suggested that QoL impairment in inherited ichthyoses may be due to a combination of factors, including physical health, daily life issues, and relationships with oneself and others 28 .…”
Section: Introductionmentioning
confidence: 99%